Perceraian Bagi Anggota Kepolisian Negara Republik Indonesia Tanpa Ijin Atasan - Solarbesain, Fransiskus Xaverius; Tjoanda, Merry; Latupono, Barzah (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: Domestic life often occurs problems with the household dipper which then causes quarrels and disputes to lead to the breakup of marriage due to divorce. Members of the National Police who want to divorce must obtain permission from their superiors, but in their implementation there are members of the National Police who can divorce in Court without the permission of their superiors.Purposes of the Research: The purpose of this study is to examine and analyze divorce procedures by members of the Indonesian National Police and the legal consequences for members of the Indonesian National Police who divorce without the permission of their superiors.Methods of the Research: This research is a normative juridical research, using a descriptive analytical research type using primary, secondary and tertiary legal sources. The approach used is a statutory approach (Statute Approach), a conceptual approach (conceptual approach) and a case approach (Case Approach). The technique of collecting legal materials uses a literature study which is then analyzed qualitatively in order to answer the problems studied.Results of the Research: Based on the results of the research, it shows that the divorce procedure for members of the Indonesian National Police has the same stages as civil society in the judicial process. However, administratively, there are formal requirements that must be met by members of the Police who wish to divorce in the form of a supervisor's permission (recommendation). Therefore, the legal consequence is if a member of the National Police who divorces without a superior's permit does not fulfill the formal requirements, therefore the lawsuit or application must be considered formally flawed so that it must be decided with an unacceptable decision or niet ontvanklijke verklaard (NO), because the formal requirements are not met, it is a violation of police regulations so that the rights of members of the National Police cannot be granted as long as they are still in the process of being violated.